Process automation instantiation for intelligence orchestration - Ramos, Edgar; Arumugam, Senthamiz Selvi (Frontiers in the Internet of Things, 2023)
The devices and use case heterogeneity in IoT make it challenging to streamline how to create processes that orchestrate devices that work interactively through actuation and sensing (data generation and data processing) toward fulfilling a goal. The question of what is needed to realize this vision using serverless technologies and leveraging semantic description tools that would eventually help to complement standards to describe such orchestration in a similar way as it is done today for microservices (e.g., using TOSCA). The article analyzes what are the different requirements that need to be present in such automation description and tests them towards some practical use cases in a particular application (vertical agriculture). The article also provides a set of analyzed instructions that might be incorporated into a description language or becomes a definition format that serves as an automation orchestration description. They provide the necessary process deployment options and interaction chains between multiple devices and data sources. These instructions are analyzed through one implementation of an execution deployment engine from the intelligence orchestration concept. Also, the practical needs and understanding of the utilization of such instructions are verified and tested with the use case.